2022
DOI: 10.1002/cam4.4600
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers expression among paired serous ovarian cancer primary lesions and their peritoneal cavity metastases in treatment‐naïve patients: A single‐center study

Abstract: Background High‐grade serous ovarian carcinoma (HGSOC), the most common histologic subtype of ovarian epithelial cancer, is associated with treatment resistance, enhanced recurrence rates, and poor prognosis. HGSOCs often metastasize to the peritoneal cavity, while fluid cytology examination could identify such metastases. This retrospective study aimed to identify potential biomarker discrepancies between paired HGSOC primary tissues and metastatic peritoneal fluid cytology samples, processed as cell blocks (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 63 publications
2
19
0
1
Order By: Relevance
“…Liu et al 10 successfully performed immunocytochemical evaluation for PD‐L1 on specimens obtained from squamous cell carcinomas of the head and neck. Other studies have shown similar success for the use of cytologic material in the evaluation of PD‐L1 expression for melanomas, 9 ovarian peritoneal specimen, 11 and pancreatic adenocarcinomas 12 …”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Liu et al 10 successfully performed immunocytochemical evaluation for PD‐L1 on specimens obtained from squamous cell carcinomas of the head and neck. Other studies have shown similar success for the use of cytologic material in the evaluation of PD‐L1 expression for melanomas, 9 ovarian peritoneal specimen, 11 and pancreatic adenocarcinomas 12 …”
Section: Resultsmentioning
confidence: 70%
“…The majority of the specimens in our review were non‐small cell lung adenocarcinomas, the review studies contained 23 melanomas, 9 21 squamous cell carcinomas of the head and neck, 10 24 cases of ovarian adenocarcinoma, 11 39 pancreatic carcinomas, 12 and 79 squamous cell carcinomas of the lung 13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EMMPRIN from mesothelial cells has been shown to induce gastric cancer cell invasion [ 42 ]. Consistent with this possible mechanism, EMMPRIN was slightly elevated when metastatic HGSOC tumors were compared with matched primary tumors [ 43 ]. Analysis of ascites would detect either tumor cell or mesothelial cell-derived factors.…”
Section: Discussionmentioning
confidence: 91%